Impelementasi Metode Annida dalam Program Menghafal Al-Qur'an di SD Plus Tahfidzul Qur'an Annida Salatiga - Ahmad Fikri Sabiq (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[Implementation of the Annida Method at Al-Qur'an Memorizing Program in SD PlusTahfizhul Quran (PTQ) Annida Salatiga]. Efforts to protect Al-Qur'an through memorization programs today have echoed everywhere. Many formal and non-formal institutions have established this program for children to adults. So there needs to be a good memorization method to be developed. The purpose of this study was to determine the method of learning to memorize the Qur'an which is applied in formal educational institutions at the elementary school level, namely the Annida method. This research method uses a qualitative approach and is field research. The technique of collecting data by means of interviews, observation, and documentation. Data analysis using qualitative analysis. The results of this study are (1) During the six years of studying at SD Plus Tahfizhul Quran (PTQ) Annida, the target students are able to memorize 10 juz. (2) The Annida method consists of four elements, namely tilawah, ziyadah, muraja'ah, and imtihan. In addition, there is also a tahfizh kit which is used as a tool to maximize the Al-Qur'an memorization program. (3) There are 30% of students from the first batch of graduates who achieved the target and 40% of students from the second generation who could achieve the target. (4) The obstacles that arise in learning tahfizh come from internal and external aspects. This research can be used as a reference for elementary level formal education institutions that develop Al-Qur'an memorization programs.